DETERMINANTS MODELING OF UNDERNUTRITION IN TODDLERS IN ACEH PROVINCE: A PLS-SEM APPROACH - Surayya, Ninda Nailis; Sirait, Timbang (PATTIMURA UNIVERSITY, 2024)
This study examines the escalating prevalence of underweight and wasting in Indonesia from 2019 to 2022. The prevalence of underweight has increased from 16.35% in 2019 to 17.1% in 2022 while wasting has increased from 7.4% to 7.7% during the same period. Aceh province faces a pressing issue of toddler malnutrition, ranking second with the highest prevalence of underweight (24.8%) and fourth highest in wasting prevalence (11.3%). According to the World Health Organization's malnutrition indicators classification, Aceh experiences notably high levels of underweight and very high levels of wasting. Employing Partial Least Squares Structural Equation Modeling (PLS-SEM) with data sourced from SSGI, publications from the Ministry of Health and BPS-Statistics Indonesia, and Aceh Provincial Food Agency, this research aims to model undernutritioned toddlers in Aceh Province. Findings reveal that undernutrition is directly affected by health access and food intake, with socioeconomic factors exerting an indirect effect. Notably, food intake emerges as the primary determinant of undernutrition.